Gender and leadership in Egypt's public sector: the case of the Ministry of Finance - El Taliawi, Ola Gamil (AUC Knowledge Fountain, 2010)
There is a radical difference in the number of males versus females in leading positions around the world, both in public and private business structures. This may reflect an underlying perception that women are not apt to lead and if put in leadership positions, they would be less competent and not as qualified as men. The purpose of this study was to answer the main research question of whether leadership style differences exist between Egyptian men and women working in the public sector in Egypt, taking the case of mid-level managers in the Ministry of Finance. The objective was to determine whether the alleged differences were based on reality or a mere perception. This would allow us either to realize that leadership style differences between men and women do exist, or to base the call for more equality in pay, promotion and opportunities for women on firmer ground that such differences are a mere stereotype. Respondents were examined on their degree of association with six aspects of leadership: Initiation of Structure, Role Assumption, Production Emphasis, Integration, Consideration, and Tolerance and Freedom. The study findings indicate that no leadership style differences exist between men and women with regards the six aspects. Women do not tend to be more Communal than men, nor do men tend to be more Agentic.